El Abiod granite (southern Rehamna - Western Meseta Morocco) - Kholaiq, Mariame (2018)
The relation between the D3 fabrics (i.e. S3 foliation and mesoscopic /macroscopic folds) and the Ras el Abiod variscan intrusion led to consider its syntectonic feature (Lagarde, 1987, Chopin et al., 2014). Indeed, they mostly wrap around the intrusion without clear cut relations, emphasizing that at least the latest D3 shortening post date the leucogranite emplacement. Such relation is very different from Sebt-Brikiini intrusion that clearly cut the D3 fabrics showing it is a post-tectonic intrusion. This shows that in Rehamna the conditions to generate granitic magmas persist at least since the 268.8±6 Ma (87Rb/86Sr, Mrini, 1985) until285 Ma (40Ar/39Ar on muscovite of Ras el Abiod: Chopin et al, 2014). Such long temporal relation between magmatism and deformation give rise to complex structural fabrics in the vicinity of Ras el Abiod granite. Southeast of Douar Nechel the S1 cleavage is affected by two crenulations with clear relations with the overgrowth minerals of the aureole of contact metamorphism. Indeed an older NNE-SSW crenulation is cut by these minerals, while an younger NNW-SSE one is deformed around them. As the trends of both lineations are close to N-S and they are more intense near the granite they could be considered as D3 fabrics (L3A and L3B respectively). Near the intrusion the S1 cleavage have been folded during D3 presenting centimetric folds with subhorizontal axial planes and low dipping axes with a vergence towards the exterior of the intrusion. Such relations indicate they should be generated during the doming induced by the granitic intrusion.